(untitled) (Jurnal Bahasa, 2024)
Language can be studied from many different angles, including pragmatics. Pragmatics is the study of interpretation of speech, including the interpretation of ambiguous and elliptical sentences. This study focuses on deixis, which refers to a word that moves or alternates, depending on the speaker, the time and the place in which the word is spoken. This study was conducted based on person deixis, which is one of the five types of deixis put forth by Levinson (1983). This study was conducted to identify the person deixis contained in the Rampai Pagi program of the district segment, as well as to describe and discuss the meaning behind the use of person deixis. The study is only focused on one of the segments contained in the Rampai Pagi program, namely the segment of Tutong, Belait and Temburong Districts, which was shown on January 20, 2020. The method used for this study is qualitative method. The results of the data analysis showed the actual use of personal pronouns—namely the first person, the second person, and the third person pronouns—which lead to the use of person deixis in the district segment’s morning show. The use of person deixis, which prioritizes the context of a conversation, makes it easier for us to know the true meaning of a conversation so as to avoid any ambiguity or confusion. By knowing the role of a personal pronoun in a conversation or speech, the interpretation of meaning becomes clearer. Keywords: Language, pragmatics, context, person deixis, pronouns Full text: PDF